2014
DOI: 10.1111/jeb.12421
|View full text |Cite
|
Sign up to set email alerts
|

Does relaxed predation drive phenotypic divergence among insular populations?

Abstract: The evolution of striking phenotypes on islands is a well-known phenomenon, and there has been a long-standing debate on the patterns of body size evolution on islands. The ecological causes driving divergence in insular populations are, however, poorly understood. Reduced predator fauna is expected to lower escape propensity, increase body size and relax selection for crypsis in small-bodied, insular prey species. Here, we investigated whether escape behaviour, body size and dorsal coloration have diverged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 83 publications
3
44
0
Order By: Relevance
“…Second, the sizes of most closely related species (e.g., Podarcis milensis and P. melisellensis, with maximum reported SVLs of 6.5 and 7.0 cm, respectively; Arnold and Ovenden 2002), are smaller than or similar to the largest mainland Skyros wall lizards (with SVLs of ;7.0 cm), whereas the largest islet lizards have SVLs of up to 9.6 cm. We have also confirmed that P ST for size is not significantly correlated with F ST (see e.g., Runemark et al 2014), and hence we can rule out that size differences between populations are a by-product of relatedness structure. Another explanation could be differences in relative contribution of age classes in the samples.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Second, the sizes of most closely related species (e.g., Podarcis milensis and P. melisellensis, with maximum reported SVLs of 6.5 and 7.0 cm, respectively; Arnold and Ovenden 2002), are smaller than or similar to the largest mainland Skyros wall lizards (with SVLs of ;7.0 cm), whereas the largest islet lizards have SVLs of up to 9.6 cm. We have also confirmed that P ST for size is not significantly correlated with F ST (see e.g., Runemark et al 2014), and hence we can rule out that size differences between populations are a by-product of relatedness structure. Another explanation could be differences in relative contribution of age classes in the samples.…”
Section: Discussionsupporting
confidence: 78%
“…Both best models (diet only and diet plus predation, respectively) include diet, and hence we can conclude that this is an important factor. Based on the fact that predation is significant in the models (Table 2), that the diet-only model did not explain data significantly better, as well as on our evidence from a previous study (Runemark et al 2014), we suggest that predation and diet both are important components for the development of island gigantism. Reduced predation pressure is known to allow organisms to obtain larger body sizes (Blanckenhorn 2000, Herczeg et al 2009) and reduced predation can also mitigate selection for early maturation, with the result that organisms attain larger adult body sizes (Rodd and Reznick 1997).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The loss or reduction of predation is one of the most common contexts in which the consequences of relaxed selection has been evaluated (Berger, Swenson, & Persson, 2001; Bleakley, Martell, & Brodie, 2006; Blumstein & Daniel, 2002; Blumstein, Daniel, Griffin, & Evans, 2000; Fullard & Ratcliffe, 2006; Fullard, Ratcliffe, & Soutar, 2004; Runemark, Brydegaard, & Svensson, 2014). Variation in predation among prey populations is relatively easy to identify (particularly at the level of presence or absence of predators; but see Reimchen, 1994), as are adaptations whose primary function is to avoid predation.…”
mentioning
confidence: 99%
“…Reduced predator fauna in islands may influence the ecology and evolution of prey species (Runemark et al. ), but predator dropout expected in islands cannot explain observed decreases in island population size. Little is known about variation in predator fauna in our study area.…”
Section: Discussionmentioning
confidence: 99%